2014
DOI: 10.1016/j.jmb.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond Barrier-Limited Chain Collapse Observed by Time-Resolved FRET and SAXS

Abstract: It is generally held that random coil polypeptide chains undergo a barrier-less continuous collapse when the solvent conditions are changed to favor the fully-folded native conformation. We test this hypothesis by probing intramolecular distance distributions during folding in one of the paradigms of folding reactions, that of cytochrome c. The Trp59 to heme distance was probed by time-resolved Förster resonance energy transfer (trFRET) in the microsecond time range of refolding. Contrary to expectation, a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 70 publications
9
52
0
Order By: Relevance
“…The latter is calculated from the known correlation between chain length (N = 81) and R g for a self-avoiding random walk (SARW), R g = 2N 0.59 (30), when corrected by 5% for the difference between the scaling for an Ala-versus Gly-containing random walk (31). Although this disordered state (under aqueous conditions) is not as expanded as a completely self-avoiding random walk, the SAXS data indicates that the reduced analog is not collapsed, consistent with findings on other unfolded proteins (32)(33)(34)(35). These results indicate that high glycine content does not necessarily produce a collapsed globule or aggregation, unlike that observed both experimentally and in simulations using poly(Gly) sequences (24-28).…”
Section: Significancesupporting
confidence: 78%
“…The latter is calculated from the known correlation between chain length (N = 81) and R g for a self-avoiding random walk (SARW), R g = 2N 0.59 (30), when corrected by 5% for the difference between the scaling for an Ala-versus Gly-containing random walk (31). Although this disordered state (under aqueous conditions) is not as expanded as a completely self-avoiding random walk, the SAXS data indicates that the reduced analog is not collapsed, consistent with findings on other unfolded proteins (32)(33)(34)(35). These results indicate that high glycine content does not necessarily produce a collapsed globule or aggregation, unlike that observed both experimentally and in simulations using poly(Gly) sequences (24-28).…”
Section: Significancesupporting
confidence: 78%
“…Equilibrium measurements were collected as previously described (28). The protein concentration was 1.5 mg·mL −1 in 10 mM potassium phosphate buffer at pH 7.0 and 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…1). Moreover, this discrepancy seems to be nearly universal among single-domain proteins: whereas the results of at least a half-dozen SAXS studies on chemically unmodified, single-domain proteins fail to detect any experimentally significant evidence (at experimental precision of, typically, a few percent) of contraction (8)(9)(10)(11)(12)(13)(14)(15), all of the more than one-dozen smFRET studies of dye-labeled, singledomain proteins reported to date have been interpreted in terms of unfolded states that contract as the denaturant concentration is lowered to ∼1 M (2,6,7,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%